Fimasartan Ameliorates Nonalcoholic Fatty Liver Disease through PPARδ Regulation in Hyperlipidemic and Hypertensive Conditions. (13th March 2017) - Lee, Yong-Jik; Jang, Yoo-Na; Han, Yoon-Mi; Kim, Hyun-Min; Jeong, Jong-Min; Seo, Hong Seog
Abstract : To investigate the effects of fimasartan on nonalcoholic fatty liver disease in hyperlipidemic and hypertensive conditions, the levels of biomarkers related to fatty acid metabolism were determined in HepG2 and differentiated 3T3-L1 cells treated by high fatty acid and liver and visceral fat tissue samples of spontaneously hypertensive rats (SHRs) given high-fat diet. In HepG2 cells and liver tissues, fimasartan was shown to increase the protein levels of peroxisome proliferator-activated receptor delta (PPAR δ ), phosphorylated 5′ adenosine monophosphate-activated protein kinase (p-AMPK), phosphorylated acetyl-CoA carboxylase (p-ACC), malonyl-CoA decarboxylase (MCD), medium chain acyl-CoA dehydrogenase (MCAD), and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1 α ), and it led to a decrease in the protein levels of 11 beta-hydroxysteroid dehydrogenase 1 (11 β -HSDH1), fatty acid synthase (FAS), and tumor necrosis factor-alpha (TNF- α ). Fimasartan decreased lipid contents in HepG2 and differentiated 3T3-L1 cells and liver tissues. In addition, fimasartan increased the adiponectin level in visceral fat tissues. The antiadipogenic effects of fimasartan were offset by PPAR δ antagonist (GSK0660). Consequently, fimasartan ameliorates nonalcoholic fatty liver disease mainly through the activation of oxidative metabolism represented by PPAR δ -AMPK-PGC-1 α pathway.